(untitled) (City: History, Culture, Society, 2018)
The University of Essex marks the centenary of the Russian Revolution with an exhibition that explores the rise and fall of the cult of Vladimir Lenin. From the exhilaration of the early Soviet years to the systematic imposition of a personality cult that was used to enforce the will of the Communist Party, FALLEN documents the inglorious fate of the Soviet Union’s deification of Lenin.